Attitudes to aging in older carers – do they have a role in their well-being?. (15th June 2015) - Loi, Samantha M.; Dow, Briony; Moore, Kirsten; Hill, Keith; Russell, Melissa; Cyarto, Elizabeth; Malta, Sue; Ames, David; Lautenschlager, Nicola T.
ABSTRACT: Background: Attitudes to aging have been investigated in non-carer populations and found to have important relationships with physical and mental health. However, these have not been explored in an older carer sample, although it is becoming increasingly important to clarify variables which are linked with positive carer outcomes. This is one of the first studies to report on older carers, their attitudes to aging, and the relationship with carer-related factors. Methods: A cross-sectional study of 202 carers with a mean age of 70.8 years was conducted in Victoria, Australia, using carer demographic data, carer factors such as depression (using the Geriatric Depression Scale), burden (using the Zarit Burden Inventory, ZBI), physical health, personality, and attitudes to aging (using the Attitudes to Aging Questionnaire, AAQ). Spearman rank correlation and hierarchical regression analyses were used. Results: This study showed that carers had overall positive attitudes to aging inspite of their caring role. It also identified that carer factors including depression and burden contributed a significant amount of the variance to attitudes to aging in terms of physical change and psychosocial loss. Personality traits, specifically neuroticism, and extraversion, were also important contributors to attitudes to aging. Conclusions: Results from this study demonstrated that inspite of moderate levels of depression and spending significant time caring, carers reported positive attitudes to aging. Treating depression, decreasing burden, and investigating the benefits of caring may assist older carers maintain their well-being.